PEMIKIRAN POLITIK DAN DAKWAH HASAN AL-BANNA - Yuni Fadilah Rahmi (Manthiq, 2017)
Abstract: The Political Thought  and  Propagation of Hasan  Al-Banna. With the  problem of how  politics  and propaganda hasan Al-banna?  and  how  the  political  contributions and  propagation of hasan Al Banna  in Indonesia? This research is a qualitative  descriptive study. This type of research is library research because this study sought  to assess and  analyze  a character, trying to trace  his ideas  through  the  works,  the  events behind the  birth.  The  results  in this  study  are  the  political  thinking  of Hasan  al-Banna,  there  are  at  least four things,  namely:  ‘Urubah (Arabism),  Wathaniyah (Patriotism), Qaumiyah (Nationalism), and’ Alamiyah (Internationalism). Eight pillars  Politics  Hasan  Al-Banna  is  as  follows:  1)  Integrated between  Islam  and politics (religion and state),  2) Inspired  of consciousness shall liberate  the homeland of Islam, 3) Inspired  of consciousness shall establish an Islamic government, 4) Established the existence of Muslims, 5) Based  the obligation  on  Islamic  unity, 6) Received  regulatory  system,  7) Criticized multiparty  and  party 8) Preserved minority groups  and foreign elementsHasan Al-Banna thought  about  propaganda. Da’wah done  by Hasan  al- Banna is as follows: 1. Forming Jama’ah Islamiyah (Al-Ihkwanul Muslims) 2. Preaching to people who do not go to the mosque to come into their homes, 3. Propagation not only through the pulpit but also through books, newspapers and  magazines, 4. Propagation among  campus. The contribution of Hasan  al-Banna  in politics and propaganda in Indonesia. Hasan al-Banna through the Muslim Brotherhood has spread its network at that time,  also raised  supports and  other  Arab countries to support  the independence of Indonesia. The Muslim Brotherhood’s role in the independence of Indonesia, it can still be traced in the article titled Brotherhood and Indonesia. In the first-order election reform later appeared Islamic parties who use the name Masjumi, such as the New Masjumi Party and the Indonesian Islamic Political Party Masjumi (PPII Masjumi). The influence of the Muslim Brotherhood to the political thinking PKS in Indonesia is very dominant through  the thought  process that is carried by the alumni  of universities  in the Middle East. The Muslim Brotherhood has an influence on political  thinking  MCC ranging  from  the  establishment of the  transform of the  missionary movement / MT becomes a party.